Triboelectric Nanogenerator with Low Crest Factor via Precise Phase Difference Design Realized by 3D Printing. Issue 12 (5th November 2021) - Hu, Yuexiao; Li, Xinyuan; Zhao, Zhihao; Zhang, Chuguo; Zhou, Linglin; Li, Yanhong; Liu, Yuebo; Wang, Jie; Wang, Zhong Lin
Abstract: Triboelectric nanogenerator (TENG) has presented the huge potential application in distributed energy field which can realize the conversion from dispersed mechanical energy to electric energy. However, the natural characteristic of pulse output for conventional TENG, which means high crest factor, is defective for directly driving electronics. Here, a strategy to convert the pulse alternate current of TENG into a direct current with low crest factor is achieved through introducing a phase difference design into the structure of TENG. As a result, a direct current with a crest factor of 1.07 is obtained in a rotational free‐standing TENG (RF‐TENG) array at optimum phase difference, where 3D digital printing technology is used to accurately control the parameter of phase difference. Moreover, an adaptable contact mode structure between tribolayer and electrode improves the durability of the RF‐TENG array, which can present a stable performance after working 1.2 million cycles. This work provides a combined strategy to obtain a long‐lifetime and low crest‐factor TENG for its large‐scale application in energy harvesting. Abstract : A direct current with low crest factor of 1.07 is realized by introducing and optimizing phase difference into the structure design of a triboelectric nanogenerator (TENG). 3D digital printing technology provides a method to accurately control the parameter of phase difference design. And an adaptable contact mode structure between tribolayer and electrode improves the durability of the rotational free‐standing TENG array.